2010
DOI: 10.1016/s0140-6736(10)62051-x
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment with zoledronic acid as compared with clodronic acid in multiple myeloma (MRC Myeloma IX): a randomised controlled trial

Abstract: SummaryBackgroundBisphosphonates reduce the risk of skeletal events in patients with malignant bone disease, and zoledronic acid has shown potential anticancer effects in preclinical and clinical studies. We aimed to establish whether bisphosphonates can affect clinical outcomes in patients with multiple myeloma.MethodsPatients of age 18 years or older with newly diagnosed multiple myeloma were enrolled from 120 centres in the UK. Computer-generated randomisation sequence was used to allocate patients equally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
390
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(415 citation statements)
references
References 31 publications
18
390
1
6
Order By: Relevance
“…Similar effect has been demonstrated with the use of zoledronic acid [93]. In fact, one randomized trial pointed to lower mortality (mostly due to reduction in early mortality) in MM patients treated with zoledronic acid when compared to patients treated with clodronic acid [94]. Radiation, typically in low doses administered in few fractions, can lead to rapid improvement in pain but should be avoided in newly diagnosed patients in nonurgent circumstances, particularly when multiple lesions are presents and large fields are required.…”
Section: Do Manage Painsupporting
confidence: 65%
“…Similar effect has been demonstrated with the use of zoledronic acid [93]. In fact, one randomized trial pointed to lower mortality (mostly due to reduction in early mortality) in MM patients treated with zoledronic acid when compared to patients treated with clodronic acid [94]. Radiation, typically in low doses administered in few fractions, can lead to rapid improvement in pain but should be avoided in newly diagnosed patients in nonurgent circumstances, particularly when multiple lesions are presents and large fields are required.…”
Section: Do Manage Painsupporting
confidence: 65%
“…Zoledronic acid was reported to reduce mortality and significantly improve PFS. 167 Patients on clodronate and zoledronic acid had similar occurrence of acute renal failure and treatment-related serious adverse events. Zoledronic acid was associated with higher rates of confirmed osteonecrosis of the jaw than was clodronic acid.…”
Section: Adjunctive Treatment For MMmentioning
confidence: 97%
“…The recent MRC Myeloma IX trial demonstrated that blocking osteoclast activity increases survival of myeloma patients. 25 Similarly, enhancing marrow stromal cell differentiation into osteoblasts decreases tumor growth and bone destruction, as well as increases bone formation. 26,27 Unfortunately, myeloma is still incurable for most patients and MMBD remains a major contributor to the morbidity and mortality of myeloma patients.…”
Section: Mechanisms Of Mmbdmentioning
confidence: 99%